Analisa Rasio Profitabilitas Dan Rasio Likuiditas (PT. Pos Indonesia) - Hafiz Assiddiqi; Hari Anugrah; Ratih Kusumastuti (Universitas 45 Surabaya, 2023)
The budget reports of an organization are assessed by investigating monetary proportions. There are several categories of financial ratios, including profitability, leverage, and liquidity ratios. This study utilizes auxiliary information acquired by implication from PT Pos Indonesia's fiscal summaries by estimating liquidity proportions (Current Proportion, Speedy Proportion and Money Proportion) and productivity proportions (Net revenue, Return on Resources and Return on Value). Financial ratios are the focus of this study, which employs a quantitative approach and a descriptive analysis model to determine whether or not the values of these ratios comply with industry standards. The evaluation of PT Pos Indonesia's financial performance reveals financial performance fluctuations or instability based on the findings of the research.